2023
DOI: 10.1136/rapm-2022-104098
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of anesthetic technique on outcomes after lumbar spine surgery: a retrospective propensity score-matched analysis of the National Surgical Quality Improvement Program, 2009–2019

Abstract: BackgroundThe impact of anesthetic technique on spine surgery outcomes is controversial. Using a large national sample of patients, we compared outcomes after lumbar decompression under regional anesthesia (RA: spinal or epidural) or general anesthesia (GA).MethodsA retrospective population-based study of American College of Surgeons National Surgical Quality Improvement Program data (2009–2019). Patients were propensity score (PS) matched 3:1 (GA:RA) on demographic and surgical variables. The primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Two large population-based studies extracted data from the National Surgical Quality Improvement Program to describe recent trends in use of neuraxial anesthesia vs. general anesthesia and to compare outcomes and complications after spine surgery according to anesthetic type [14 ▪▪ ,15 ▪▪ ]. The first reported trends in the use of general anesthesia and non-general anesthesia among 301 521 patients undergoing all types of spine surgery, including lumbar, thoracic and/or cervical procedures (2005--2019) [14 ▪▪ ].…”
Section: Retrospective Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two large population-based studies extracted data from the National Surgical Quality Improvement Program to describe recent trends in use of neuraxial anesthesia vs. general anesthesia and to compare outcomes and complications after spine surgery according to anesthetic type [14 ▪▪ ,15 ▪▪ ]. The first reported trends in the use of general anesthesia and non-general anesthesia among 301 521 patients undergoing all types of spine surgery, including lumbar, thoracic and/or cervical procedures (2005--2019) [14 ▪▪ ].…”
Section: Retrospective Studiesmentioning
confidence: 99%
“…The authors found progressive utilization of non-general anesthesia over time for all subtypes of spine surgery together with significant reductions in length of hospital stay, readmission and 30-day complications among patients undergoing lumbar spine surgery. The second study assessed the impact of anesthetic technique on outcomes after lumbar decompression under spinal or epidural anesthesia compared to general anesthesia in 151 010 patients (2009--2019) [15 ▪▪ ]. Compared with general anesthesia, neuraxial anesthesia was associated with fewer complications, less blood transfusion and shorter length of stay after surgery, without significant differences in readmission.…”
Section: Retrospective Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such Clinical recommendations are often based on evidence derived from meta-analysis of randomized controlled trials (RCTS) but their interpretation is often hindered by the fact that they do not always consider current clinical relevance ( 9 ). Recently, a few studies have found that the use of regional blocks can reduce the incidence of postoperative complications in patients with real data ( 10 ), however, the findings are more limited to orthopedic surgery and do not grade the severity of complications in them ( 11 , 12 ). The same complications may have different levels of severity with different levels of management.…”
Section: Introductionmentioning
confidence: 99%
“…Recent case reports after a terminated prospective trial should be a warning to all that FPBs' relative safety is not absolute. 24…”
mentioning
confidence: 99%